Level of empathy in nursing students at a private university in Chiclayo, 2022 - Sánchez Castro, Yexsy Sara (2024)
Objective: Determine the level of empathy in nursing students at a private university in Chiclayo, 2022. Method: Quantitative, non-experimental, transactional, descriptive research; With a population of 118 nursing students from the VII, VIII, IX and X academic cycle of 2022-I, the sample was 87 students, stratified and simple random sampling. For data collection, a survey was used, and the Jefferson medical empathy scale instrument with a Cronbach's alpha of 0.751, with a validity of KMO (0.357) and Bartlett Test (0.000). It was carried out virtually asynchronously through Google Forms with an approximate time of 20 minutes. For data analysis, the spreadsheet of the Excel program was used, through descriptive statistics. Main results: 60% of students achieved a high level of empathy, highlighting the students of the VII cycle with 68%. Regarding the dimension, compassionate care and putting oneself in the other person's place in general obtained a low level of empathy with 2% and 17% respectively. In the age of 25 to 26 years, 90% reached a high level. General conclusion: The students of the Santo Toribio de Mogrovejo Catholic University, from the nursing school, mostly have a high level of empathy, because they receive training that allows them to develop their empathic skills, they are more in contact with patients in their clinical practices, they are also interested in their nursing career. Keywords: Empathy (D004645), students (D013334) and nursing (Q000451)